Pearl millet and sorghum improvement in India - Pray, Carl E.; Nagarajan, Latha (International Food Policy Research Institute, 2009)
The spread of modern varieties and hybrids of pearl millet and sorghum that began in the mid-1960s has had an important impact on small farmer welfare in India. The success and sustainability of these improved cultivars resulted from three types (or periods) of interventions by the Indian government: (1) increased investments in crop improvement by national and international agricultural systems during the 1970s; (2) development of efficient seed systems, with the gradual inclusion of the private sector in the 1980s; and (3) the liberalization of the Indian seed industry in the late 1990s. In addition to increased overall production levels of sorghum and millet, there have been substantial yield gains in semi-arid regions as well as improved cultivars adopted in some of the poorest areas of India. The innovations of new, hybrid technology have not been limited to the Green Revolution crops; they have also had significant impact on the productivity of small-farmer households growing dryland crops, such as millet and sorghum in India.